2020
DOI: 10.1007/s42452-020-2618-2
|View full text |Cite
|
Sign up to set email alerts
|

IR spectroscopic and photoluminescence studies of plasma polymerized organic thin films based on tea tree oil

Abstract: Plasma-assisted synthesis of transparent, environment friendly, lightweight, flexible and stable organic thin films from naturally occurring precursors were emerging as potential candidates for organic semiconductor industry. In the present study, tea tree (Malaleuca alternifolia) oil based polymer thin films were deposited on glass and silicon substrate by using radio frequency plasma polymerization technique. The polymer thin films were characterized with atomic force microscopy (AFM) and Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…IR spectroscopy showed that band maxima shifted depending on the substrate used, indicating a variation in bond lengths depending on the substrate and showing that amorphous glass substrates are better scaffolds for plasma polymer growth than crystalline silicon substrates. [ 91 ] Bazaka et al were the first to examine the effects of plasma treatment with Ar APPJ on thin films from tea tree oil plasma polymers upon PET substrates. Compared to as‐deposited plasma polymers, APPJ‐treated plasma polymers showed increased surface oxidation, with three potential oxygen sources being: fragments of oxygen moieties from retained precursor molecules, coating exposure to ambient air and reactions between Ar plasma and ambient air.…”
Section: Pecvd Of Biogenic Precursorsmentioning
confidence: 99%
“…IR spectroscopy showed that band maxima shifted depending on the substrate used, indicating a variation in bond lengths depending on the substrate and showing that amorphous glass substrates are better scaffolds for plasma polymer growth than crystalline silicon substrates. [ 91 ] Bazaka et al were the first to examine the effects of plasma treatment with Ar APPJ on thin films from tea tree oil plasma polymers upon PET substrates. Compared to as‐deposited plasma polymers, APPJ‐treated plasma polymers showed increased surface oxidation, with three potential oxygen sources being: fragments of oxygen moieties from retained precursor molecules, coating exposure to ambient air and reactions between Ar plasma and ambient air.…”
Section: Pecvd Of Biogenic Precursorsmentioning
confidence: 99%